The safety of fondaparinux, enoxaparin, and unfractionated heparin in COVID-19 patients - Siti Aulia Musyrifah; Endro Nugroho, Agung; Fita Rahmawati (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2024)
The coagulopathy, a hematological disorder affecting blood clotting, carries an elevated risk of thrombosis and mortality in COVID-19 patients. Fondaparinux, enoxaparin, and unfractionated heparin (UFH) are potential treatments for reducing coagulopathy in COVID-19 patients. Nonetheless, anticoagulant administration increases the risk of bleeding-related adverse effects. This study aimed to evaluate the safety profile of fondaparinux, enoxaparin, and UFH in COVID-19 patients. The safety was evaluated based on the prevalence of major and minor bleeding events from the data of medical records collected retrospectively from October 2022 to December 2021 at Kediri District Hospital. The Chi-square analysis and multiple logistic regression were employed to establish associations between variables. Out of the 315 patients who meet the inclusion criteria, 35 patients (11.1%) exhibited bleeding, 11 patients (3.5%) experienced major bleeding, while 24 patients (7.6%) encountered minor bleeding. No significantly different in bleeding events both major and minor bleeding among the groups receiving fondaparinux, enoxaparin, and UFH were observed (p> 0.05). The UFH emerged as the most common anticoagulant associated with bleeding incidents. The multivariate analysis revealed that age ≥ 60 yr and concomitant medication with ketorolac influenced bleeding incidence. The monitoring of bleeding events on the use of anticoagulants is necessary.